2013
DOI: 10.4081/oncol.2013.226
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal therapy in metastatic prostate cancer: current perspectives and controversies

Abstract: Ever since the introduction of androgen deprivation therapy (ADT) in prostate cancer, various controversial aspects of hormonal therapy have come to light. There has been tremendous progress in this area, marked by several important developments in the availability of various new androgen-suppressing agents and refinements to the existing therapies. Parallel to these developments, various more debatable aspects have arisen in the use of these therapies with regards to their negative impact on quality of life p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Regional reports from Nigeria indicate that 40%-51.3% of patients with PCa present with metastasis, and up to 94.2% have locally advanced disease at presentation [4,5]. Despite the proven cost and survival benefits of surgical over medical castration [6][7][8], studies in other regions have shown either null difference or preference for medical castration over surgical castration [9][10][11]. Such preferences have been in a bid to avoid surgery or a negative body image due to an empty scrotum [8,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Regional reports from Nigeria indicate that 40%-51.3% of patients with PCa present with metastasis, and up to 94.2% have locally advanced disease at presentation [4,5]. Despite the proven cost and survival benefits of surgical over medical castration [6][7][8], studies in other regions have shown either null difference or preference for medical castration over surgical castration [9][10][11]. Such preferences have been in a bid to avoid surgery or a negative body image due to an empty scrotum [8,9,12].…”
Section: Introductionmentioning
confidence: 99%